2006
DOI: 10.1002/14651858.cd003521.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative therapies for pain management in labour

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(38 citation statements)
references
References 44 publications
0
30
0
8
Order By: Relevance
“…We conducted the study because the effect of acupuncture on labor pain was poorly documented. All studies published before 2002 were small, retrospective, or uncontrolled (5)(6)(7)(8)(9)(10)(11), and only a few randomized controlled trials have evaluated the effectiveness of acupuncture for pain relief during labor since 2002 (17)(18)(19)(20)(21)(22)(23)(24)(25). These studies vary in size and quality.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the study because the effect of acupuncture on labor pain was poorly documented. All studies published before 2002 were small, retrospective, or uncontrolled (5)(6)(7)(8)(9)(10)(11), and only a few randomized controlled trials have evaluated the effectiveness of acupuncture for pain relief during labor since 2002 (17)(18)(19)(20)(21)(22)(23)(24)(25). These studies vary in size and quality.…”
Section: Discussionmentioning
confidence: 99%
“…This would require a comparison between massage with relaxation techniques and relaxation techniques alone, practised by women and their birthing partners from 36 weeks gestation until birth. To improve the quality of evidence on massage interventions combined with relaxation techniques for labour and birth pain, our key task is to follow recent recommendations, to correct design flaws and methodological weakness in existing trials (Smith et al, 2006;Ezzo, 2007). The majority of recent trials on massage for labour and other forms of pain have been designed to test the effects of structured programmes of massage used in combination with other techniques (Field et al, 1997;Chang et al, 2002;Yildirim and Sahin, 2004;Ezzo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…14 A systematic review of the use of CAM for pain management in labour reported one aromatherapy randomised controlled trial (RCT). 15 This very small study of 22 women comparing one essential oil (EO) with another on maternal pain perception during labour failed to detect any significant difference for any outcome. 16 The use of aromatherapy in labour was explored in an observational study undertaken in a district general maternity unit in the UK and involving a sample of 8053 participants.…”
Section: Introductionmentioning
confidence: 95%